PENERAPAN ALGORITMA PROMETHEE DALAM PENILAIAN KINERJA DOSEN - Fallo, Diana Yani; Benufinit, Yonly; Sogen, Maria (FKIP Universitas Citra Bangsa, 2024)
Abstract: This research focuses on the implementation of performance assessment for lecturers at the Faculty of Education and Teacher Training (FKIP) of Citra Bangsa University. Lecturers are expected to demonstrate good performance because educational institutions play a role in producing quality human resources. Performance appraisals generally aim to provide feedback or feedback to employees in an effort to improve work performance, increase the productivity of an organization, and are specifically carried out in relation to various policies towards employees, such as for the purpose of promotion or giving awards. The Promethee method can make decisions based on calculations conducted on each criterion. There are seven (7) criteria used in this research. The results obtained are a net flow value of 0.238095 for lecturer E and the lowest value is found for lecturer A with a value of -0.09524. According to the calculations conducted, it is found that lecturers E, B, and D are recommended for having good performance. Abstrak Penelitian difokuskan pada implementasi penilaian kinerja dosen FKIP Universitas Citra Bangsa. Dosen dituntut untuk dapat menunjukkan kinerja yang baik hal ini karenakan lembaga pendidikan memiliki peran dalam menghasilkan sumber daya yang berkualitas. Penilaian kinerja secara umum bertujuan untuk memberikan feedback atau timbal balik kepada karyawan dalam upaya memperbaiki tampilan kerja, meningkatkan produktivitas suatu organisasi, dan secara khusus dilakukan berkaitan dengan berbagai kebijaksanaan terhadap karyawan, seperti untuk tujuan promosi jabatan atau memberikan penghargaan. Metode Promethee dapat menghasilkan keputusan berdasarkan perhitungan yang dilakukan pada masing-masing kriteria. Kriteria yang digunakan dalam penelitian ini ada 7 kriteria. Hasil yang diperoleh dosen E yaitu nilai net flow sebesar 0,238095 dan dosen yang memiliki nilai rendah terdapat pada dosen A dengan nilai -0,09524. Dari hasil perhitungan yang dilakukan dapat ditemukan bahwa dosen E,B,D yang direkomendasikan dengan memiliki kinerja yang baik.